Analysis Method for Estimating Diffuseness of Sound Fields by Using Decay-Cancelled Impulse Response. Issue 2 (June 2014) - Hanyu, Toshiki
An analysis method for estimating diffuseness of sound fields by measuring the time variation in reflected sound energy of impulse responses is proposed. In this method, first a decay-cancelled impulse response is obtained by removing the reverberation decay from the impulse response using a Schroeder decay curve. The degree of diffusion of the sound field is determined by evaluating the time variation in the reflected sound energy of the decay-cancelled impulse response. By using this method, the frequency characteristics of diffuseness in sound fields can be analysed from the impulse response measured at a single point. The average degree of diffusion in a room can also be evaluated by averaging the analysis results at several points in the room, similar to the analysis of reverberation time. In order to verify the proposed method, the impulse responses in rooms having different types of diffusers were calculated by the wave acoustics computer simulation. The frequency characteristics of diffuseness were analysed from the calculated impulse responses, by using the proposed method. The results showed that the frequency characteristics of diffuseness change depending on the size of the diffusers. Thus, the proposed method can be used for evaluating the effect of diffusers on the degree of diffusion in a sound field.